Implementation of project based learning containing esd to improve students' creative thinking skills - Purnamasari, Adetia Yeyen; Rustaman, Nuryani; Purwianingsih, Widi; Lestari, Weni (JPPI (Jurnal Penelitian Pendidikan Indonesia), 2024)
21st century learning demands critical thinking, creativity, collaboration and communication competencies. Therefore, integrating 21st century skills into the learning process effectively is very important, both teachers and students are expected to be able to master these skills. However, there are still many students who have not mastered 21st century skills, one of which is creative thinking skills. To achieve this competency, students need to experience a supportive process, active learning, and involve the problems around them, one of which is learning using PjBL which contains ESD. The data collection technique uses case-based essay questions about the diversity of wild plants in the area. Data were analyzed using the N Gain test, normality test, homogeneity test and hypothesis test. The research was conducted over five meetings with the implementation of PjBL containing ESD which aims to improve students' creative thinking skills. The results of the research that has been carried out show that the creative thinking skills of students in the experimental group obtained an average N Gain value of 0.58 in the medium category, while in the control group an N-Gain value of 0.25 was obtained in the low category. So it can be concluded that the use of the PjBL model containing ESD can improve students' creative thinking skills.